KOMPARASI POLIGAMI DAN MONOGAMI DALAM PERSPEKTIF HUKUM ISLAM - Feny Dyah Aprillia; Vivien Indrawati Setya (Indonesian Journal of Law and Islamic Law (IJLIL), 2019)
Islam came to the surface of the earth by bringing some shari'a or order of life for humans, so that their lives are safe and happy in the world until the hereafter. Including those brought by Islam through the Prophet Muhammad. in the form of marriage law. Marriage is sunnatullah where men need a female companion and vice versa. The companion referred to here is a companion as a legal husband and wife who are bound by the 'aqdun nikah bond according to the Islamic order. But in reality, the practice of marriage that occurs at this time has experienced dynamics and variations in the arguments of the fuqaha 'ulama, especially regarding the permissibility of a husband to be polygamous or monogamous. According to some scholars, men are allowed to marry more than one woman on condition that they are able to be fair to their wives, while according to other scholars, polygamy is not legal because it is impossible to achieve a fair attitude, especially fairness with feelings.